Traumatismo dentário com luxação intrusiva com acompanhamento de seis anos: relato de caso clínico: RELATO DE CASO CLÍNICO (Revista da Faculdade de Odontologia - UPF, 2020)
Objective: This study is designed to report a clinical intrusion case, which exhibited enamel hypoplasia on the crown of tooth 11 and which underwent clinical and X-ray monitoring for six years. Case report: A three-year-old female patient exhibited intrusion of deciduous teeth 51, 52, 61, and 62. After X-ray, it was detected that teeth 51 and 61 had perforated the nasal cavity floor, but all four teeth had re-erupted and began to be monitored. After six months, teeth 51 and 61 exhibited bone loss in the interproximal area, as well as mobility, which led to tooth extraction. Teeth 52 and 62 re-erupted in a satisfactory position, and exhibited no signs and symptoms of infection, periapical alteration, or mobility. These teeth were therefore maintained in the arch. After six years, it was detected that tooth 11 had erupted with enamel hypoplasia. Final considerations: Long-term clinical and X-ray control proved essential, as it allowed for the early diagnosis of potential alterations, and minimized potential sequelae to the permanent teeth.